Pemanfaatan Kombinasi Air Cucian Beras, Cangkang Telur Ayam, dan Kulit Pisang Kepok sebagai Pupuk Organik Cair untuk Pertumbuhan Tanaman Sawi Hijau (Brassica juncea L.) - ., Ira Mahrita; ., Mella Mutika Sari; ., Sauqina (CV. ITTC INDONESIA, 2023)
Utilization of organic waste rice washing water, chicken eggshells, and kepok banana peels as liquid organic fertilizer can reduce environmental pollution because it can be used to increase the availability of nutrients in plants. This research aims to determine the effect of liquid organic fertilizer fermented rice washing water, chicken eggshells and kepok banana peels on mustard greens (Brassica juncea L.) seen from plant height and number of leaves produced. This experimental research used a completely randomized design (CRD) consisting of five treatments and four repetition. Treatment of green mustard plants was given different concentrations, namely (P1 = control), (P2 = 100 ml/L), (P3 = 125 ml/L ), (P4 = 150 ml/L), and (P5 = 175 ml/L). SPSS statistical data analysis technique by conducting the Anova test at the 5% level. The results showed that the average increase in height and number of leaves of mustard greens was relatively the same in all treatments with the highest average obtained at concentration (P2 = 100 ml/L).